Dampak Ilegal Driling Terhadap Kerusakan Lingkungan Di Kabupaten Batanghari (Studi Kasus Ilegal Driling Di Desa Pompa Air Kecamatan Bajubang Kebupaten Batanghari - Prawiratama, Radytia; Akmal Latif, Syahrul (SISI LAIN REALITA, 2022)
Oil is fuel that widely used in various aspect in life including engine propulsion, so oil is very valuable commodity and causes economic life to improve, therefore interest in the oil sector is quite high and vulnerable to crime. Crime that happened is smuggling oil, oil theft, ilegal drilling, like happened on Pompa Air vilage ilegal drilling make environmental damage. This research use green criminology theory that issues about environmental damage, with qualitative method and description method mean to describe this research problem.